Health and wellness for life - Potočnik, Bernarda (knjige, 2021)
Welcome to the course of English. So far you have probably already had quite a lot of experience with the English language. Now it is time to improve your communication skills, repeat grammar and add new words to your vocabulary, especially from the area of wellness and healthy lifestyle.
Keywords: Angleščine; elektronske knjige; Terminologija; Učbeniki za višje šole; Velnes